Strategy for Developing Student Cognitive Aspects: Internet-Based Islamic Education Learning Innovation During the COVID-19 Pandemic - Redy Eka Yudesthira; Hafidh Ali Masjid; Didit Prasetyo; Jefry Hadi Susilo Ramada (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is strategy for developing student cognitive aspects of internet-based islamic education learning innovation during the coronavirus disease 2019 (COVID-19) pandemic. The research approach used in this research is qualitative research, while the type of research is a case study. The research location uses a multi-case study, namely MTs Hasyim Asy'ari Batu City and MAN 01 Malang City. There are two types of data and sources of data in this study, namely primary and secondary data. The data analysis technique used in this study is the Miles, Hiberman, and Saldana model. The results show that internet-based islamic education learning innovation during the coronavirus disease 2019 (COVID-19) pandemic is to evaluate learning, foster student learning motivation, provide feedback in learning as well as teacher creativity and innovation in using models and methods.